Transphobia as a social disease: discourses of vulnerabilities in trans men and transmasculine people - Bernardo Haylan de Souza do Carmo Lobo; Gabriele da Silva Santos; Carle Porcino; Tilson Nunes Mota; Felipe Aliro Machuca-Contreras; Jeane Freitas de Oliveira; Evanilda Souza de Santana Carvalho; Anderson Reis de Sousa (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to analyze the repercussions of transphobia on trans men's and transmasculine people's health. Method: a qualitative study carried out with 38 participants, 35 trans men and three trans men, who attended specialized transgender health services in Bahia, Brazil. In-depth interviews were carried out between June 2019 and February 2020. The Discourse of Collective Subject technique was used and interpretation based on the theoretical concept of transphobia. Results: transphobia has intra and interpersonal repercussions on the life and health of trans men and transmasculine people who attend health services. There were experiences of violence in the private space, fraying of family ties; discrimination in the school space; limitation in professional/work opportunities; barriers to self-care and access to health services; elaboration of trans identity protection strategies; consequences of transphobia on psycho-emotional health. Conclusion: transphobia is a social disease that affects different life and health dimensions. It causes damage to the socialization of trans men and transmasculine people, in addition to health service spaces as well as in family environments, schools, universities and at work, which result in non-adherence to self-care, distancing from health services and psycho-emotional distress.